Wireless Sensor Networks 9th European Conference, EWSN 2012, Trento, Italy, February 15-17, 2012. Proceedings - Picco, Gian Pietro; Heinzelman, Wendi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 9th European Conference on Wireless Sensor Networks, EWSN 2012, held in Trento, Italy, in Februar 2012. The 16 revised full papers presented were carefully reviewed and selected from 78 submissions. The papers are organized in topical sections on communication and security, system issues, reliability, localization and smart cameras, and hardware and sensing.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Computer simulation; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Programming Techniques; Software Engineering; Information Systems Applications (incl. Internet).; Simulation and Modeling